Analisis Dampak Investasi Infrastruktur Terhadap Pertumbuhan Ekonomi Daerah: Studi Kasus di Provinsi Nusa Tenggara Barat - Andreas Bahari; Misbahul Ulum; Ananda Murad (Economica Insight, 2025)
Infrastructure investment plays a crucial role in driving regional economic growth, particularly in developing regions such as West Nusa Tenggara (NTB) Province. Adequate infrastructure can increase productivity, accelerate the distribution of goods and services, and attract private investment. This study aims to analyze the impact of infrastructure investment on regional economic growth in NTB in 2025. The research method uses a descriptive quantitative approach with secondary data obtained from the Central Statistics Agency (BPS), the NTB Public Works and Housing Agency (PUPR), and regional financial reports. The results show that increased investment in the road, energy, and tourism sectors significantly contributes to the increase in NTB's Gross Regional Domestic Product (GRDP). Infrastructure investment in NTB has been shown to have a strong multiplier effect on the trade, agriculture, and tourism sectors.